2005
DOI: 10.1002/ar.a.20236
|View full text |Cite
|
Sign up to set email alerts
|

Stereology and ultrastructure of the salivary glands of diabetic Nod mice submitted to long‐term insulin treatment

Abstract: Insulin-dependent diabetes mellitus compromises the salivary glands, altering their morphology and the mechanisms of salivation, which are fundamental for oral health. Thus, the aim of the present study was to determine the effects of prolonged insulin treatment on the morphology of the salivary glands in Nod mice. Forty-five female mice were divided into five groups: nine positive diabetic Nod mice for 10 days (group 1), nine positive diabetic Nod mice for 20 days (group 2), nine diabetic Nod mice for 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…Most investigations were focused on salivary glands with sialadenosis, namely with a severe grade of atrophy and cell degeneration. On the other hand, experiments on rats with induced diabetes and Nod mice showed that submandibular gland features are still affected or only partly restored when glycemic level was controlled by insulin treatment . Our results show that diabetes causes significant changes in human submandibular gland even when glycemia is well controlled and clinical signs of gland malfunctions are absent.…”
Section: Discussionmentioning
confidence: 60%
“…Most investigations were focused on salivary glands with sialadenosis, namely with a severe grade of atrophy and cell degeneration. On the other hand, experiments on rats with induced diabetes and Nod mice showed that submandibular gland features are still affected or only partly restored when glycemic level was controlled by insulin treatment . Our results show that diabetes causes significant changes in human submandibular gland even when glycemia is well controlled and clinical signs of gland malfunctions are absent.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies observed high serum glucose levels in diabetic rodents [30]. Sodium selenite had been found to significantly decrease the high blood glucose level observed in diabetes [31].…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that these reported alterations began with increased synthesis of laminin and other matrix proteins. Caldeira et al (2005), studying non- Parotid glands of control (C), 30 days diabetic (D30) and 60 days diabetic (D60) rats were submitted to immunofluorescence for different ECM proteins. Initial labeling for each protein was considered (+), and alterations observed in diabetes (++ for medium and +++ for high) were compared to the initial control.…”
Section: Discussionmentioning
confidence: 99%